Circumventing the “Ick” Factor: A Randomized Trial of the Effects of Omitting Affective Attitudes Questions to Increase Intention to Become an Organ Donor - Doherty, Sally; Dolan, Elizabeth; Flynn, Jennifer; O’Carroll, Ronan E.; Doyle, Frank (Frontiers in Psychology, 2017)
Objectives: Including or excluding certain questions about organ donation may influence peoples’ intention to donate. We investigated the effect of omitting certain affective attitudinal items on potential donors’ intention and behavior for donation. Design: A cross-sectional survey with a subgroup nested randomized trial. Methods: A total of 578 members of the public in four shopping centers were surveyed on their attitudes to organ donation. Non-donors (n = 349) were randomly assigned to one of three groups: Group 1 completed items on affective and cognitive attitudes, anticipated regret, intention, subjective norm and perceived behavioral control. Group 2 completed all items above but excluded affective attitudes. Group 3 completed all items but omitted negatively worded affective attitudes. The primary outcome was intention to donate, taking a donor card after the interview was a secondary behavioral outcome, and both were predicted using linear and logistic regression with group 1 as the reference. Results: Mean (SD) 1–7 intention scores for groups 1, 2 and 3 were, respectively: 4.43 (SD 1.89), 4.95 (SD 1.64) and 4.88 (SD 1.81), with group 2 significantly higher than group 1 (β = 0.518, 95% confidence interval [CI] 0.18 to 0.86).At the end of the interview, people in group 2 (66.7%; OR = 1.40, 95% CI 0.94 to 2.07, p = 0.096) but not those in group 3 (61.7%; OR = 1.10, 95% CI 0.69 to 1.75, p = 0.685), were marginally more likely to accept a donor card from the interviewer than people in group 1 (59.7%). Conclusion: Omitting affective attitudinal items results in higher intention to donate organs and marginally higher rates of acceptance of donor cards, which has important implications for future organ donation public health campaigns.